Groundwater Pollution Connected to Multiple Effect: A Case Study Kaman (Kırşehir, Turkey) - Tülay Ekemen Keskin; Bahadır Subaşı; Feyza Girişen; Zeynel Başıbüyük (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
This study aim to detect the groundwater pollution connected to multiple effect such as the interaction of mineral/ore-water, mining destruction and agricultural activities in Kaman (Kırçehir). The study area has recently abondoned iron, antimony, gold and floride mine areas and so, there are a lot of mine piles. Mine waste is a rich source of hazardous trace elements to the environment. In many areas expecially abandoned sulphidic mine wastes may cause to produce acid mine drainage. Although no acid mine drainage is observed in the study area, the region needs to be reworked for this purpose in the following years. The electrical conductivity, pH and Eh values of the waters range between 126-1994 μS/cm; 7.28-8.58; 222-649 mV respectively. In the rainy season, the pH values of the waters decreased due to the effect of slight acidic precipitation and in parallel with this decrease, EC, TDS, Ca, Na, SO4, HCO3, As, Sb, U concentrations of some waters increase due to the increase of solubility of elements. As, Sb, F, U, NO3, NH4 concentrations some of water exceed the maximum limit values given in the Turkish and World Health Organization Standards. Especially As contamination is a big problem for the region, because of tens of times exceed drinking water regulations.